Educação sexual orientada para a ação: um estudo bibliográfico sobre a aplicabilidade dessa modalidade de intervenção - Dias, Robinson Alves [UNESP] (2014)
In this study, we focused on the sexuality related to health, which takes on a different role on the decisions for a healthier lifestyle. We attempted to outline some aspects of child and adolescent sexuality, with more emphasis on adolescence. This research involves health, so we presented an overview of nursing formation, its constructions, legacy and difficulties on dealing with human sciences. We also presented a small picture of the sexual identity of students in Brazilian and Portuguese schools, and the differences between these countries. Methodologically, this is an innovative and pioneer study in Brazil, and the literature review was used to expose the study of the Portuguese researcher Vilaça (from the University of Minho – Portugal), which is anchored on the S-IVAM methodology (Problem selection = Investigation, Vision, Action and Changes) having as concepts the Health Promoting Schools, linked to the Democratic Paradigm for Health Education (proposed by the Danish researcher Jensen). The focuses are the main points that comprise the new methodology, bio-holism: sex education with active participation of all school components, positive construction for a healthier future and the insertion of students in environmental care, respect for people, family and society, the acquisition of new knowledge and a healthier lifestyle. We can conclude that it is possible to implant the methodology in Brazilian schools and that sex education, when it overcomes the stigma of sex, will be the basis for better management and leadership, with respect for students, for the construction of a better future, with respect to differences and human beings